2016
DOI: 10.1038/mtna.2016.103
|View full text |Cite
|
Sign up to set email alerts
|

E-selectin Targeting PEGylated-thioaptamer Prevents Breast Cancer Metastases

Abstract: E-selectin is an adhesion molecule expressed on the luminal surface of inflamed blood vessels that mediates hematogenous metastasis by assisting shear-resistant adhesion of circulating tumor cells to the vessel surface under dynamic blood flow. Previously, we developed an E-selectin antagonistic thioaptamer (ESTA) for the prevention of hematogenous metastasis through the blockade of CD44 breast cancer cells (BCa) adhesion to E-selectin-expressing premetastatic endothelial niche. The current study focuses on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…Similarly, conjugation of 40 kDa PEG to a 2′-fluoro-/2′- O -methyl modified aptamer resulted in an increase of the circulation half-life to 23 h in a mouse model [ 48 ]. However, high molecular weight PEG conjugation may cause a functional hindrance of the aptamer binding to its target [ 62 ]. Thus the size of PEG as well as type and length of linkage of PEG to aptamer should be determined in a case-by-case fashion.…”
Section: Challenges and Possible Solutions In Aptamer Therapeuticsmentioning
confidence: 99%
“…Similarly, conjugation of 40 kDa PEG to a 2′-fluoro-/2′- O -methyl modified aptamer resulted in an increase of the circulation half-life to 23 h in a mouse model [ 48 ]. However, high molecular weight PEG conjugation may cause a functional hindrance of the aptamer binding to its target [ 62 ]. Thus the size of PEG as well as type and length of linkage of PEG to aptamer should be determined in a case-by-case fashion.…”
Section: Challenges and Possible Solutions In Aptamer Therapeuticsmentioning
confidence: 99%
“…It has been shown that E-selectin assists shear-resistant adhesion of circulating tumor cells to the vessel surface under dynamic blood flow [32]. Furthermore, SCF is a potent chemokine that favors recruitment of cancer-stem cells and other inflammatory cells including MDSCs [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…在小鼠研究 中, 人们发现将2′氟-/2′-氧甲基修饰的核酸适配子与 40 kDa的PEG缀合, 能使其半衰期增加至23 h [133] . 然 而, 高分子量PEG缀合也可能影响适配子与靶标分子 的结合 [144] . .…”
Section: 以抗人肿瘤坏死因子Tnf的rna适配子为例 未经修unclassified